GMAT, GGPA, and Conscientiousness as Predictors of Career Success - Miao, Chao; Kahle-Piasecki, Lisa; Qian, Shanshan (Journal of Management Policy and Practice, 2017)
The Graduate Management Admission Test (GMAT) has drawn more attention than ever before in business graduate programs because GMAT scores are weighted heavily in the admission process. Primary as well as meta-analytic studies have corroborated that GMAT is a valid predictor of academic performance in business graduate programs. However, little attention has been paid to GMATs validity in predicting career success. The present research fills this research gap by conceptually investigating the interplay among GMAT scores, graduate grade point average (GGPA), conscientiousness, and career success